ChemInform Abstract: Room Temperature N‐Arylation of Amino Acids and Peptides Using Copper(I) and β‐Diketone. Issue 33 (August 2015) - Sharma, Krishna K.; Sharma, Swagat; Kudwal, Anurag; Jain, Rahul
Abstract A high yielding, general method for the N‐arylation of zwitterionic amino acids, amino acid esters, and peptides is described.